Front Cover: One Scaffold, Different Organelle Sensors: pH‐Activable Fluorescent Probes for Targeting Live Microglial Cell Organelles (ChemBioChem 9/2022). (16th December 2021) - Jethava, Krupal P.; Prakash, Priya; Manchanda, Palak; Arora, Harshit; Chopra, Gaurav
Abstract : One scaffold – different organelle sensors : The structure‐organelle relationship (SOR) of an important synthetic intermediate targeting the nucleus and its transformation into other pH‐activable fluorescent probes is demonstrated. The fluorescent probes were synthesized using a single synthetic route. As shown in the cover picture, the assembly line illustrates that a common synthetic intermediate (rectangle shape) was transformed into another molecule (triangle or hexagonal shape) in a one‐step reaction to target specific cell organelles in live microglial cells. The common intermediate targets the cell nucleus, the cationic probe targets mitochondria, whereas the amine‐containing probe with pH‐activable property targets acidic lysosomes. The graphic was created by Ryann Davis. More information can be found in the Communication by G. Chopra et al.